Analytical and numerical modelling of elastic properties of isotropic and anisotropic rocks and their stress dependencies - Golodoniuc, Pavel (Curtin University, 2015)
The research is focused on analytical and numerical modelling of elastic properties of rocks and their stress dependencies. A number of approaches to model and simulate stress dependencies of elastic properties of rocks were tested. Proposed models were, at first, tested on isotropic rocks and then further developed to anisotropic case and applied to shales. The study was supported by the numerical simulations using Finite Element Method on realistic 3D models reconstructed from computer tomography images.